Integrin-mediated adhesion of uterine endometrial cells from endometriosis patients to extracellular matrix proteins is enhanced by tumor necrosis factor alpha (TNFα) and interleukin-1 (IL-1) - Sillem, Martin; Prifti, Sophia; Monga, Bondo; Arslić-Schmitt, Tatjana; Runnebaum, Benno (European journal of obstetrics & gynecology and reproductive biology, 1999)
(1) to demonstrate specificity of integrin function in endometrial cell adhesion; (2) to investigate their regulation by tumor necrosis factor alpha (TNFα) and interleukin-1 (IL-1); and (3) to detect differences between cells from patients with and without endometriosis.
Gesehen am 20.11.2020